FTA Highlight No.1 – Introduction: Ten Years of Forests, Trees and Agroforestry Research in Partnership for Sustainable Development - Noordwijk, M. van; Gitz, V.; Nasi, R.; Baral, H.; Belcher, B.; Boot, R.; Brady, M.A.; Duchelle, Amy E.; Duguma, L.A.; Elias, M.; Fa, J.E.; Gracia, E.; et al. (CGIAR Research Program on Forests, Trees and Agroforestry, 2021)
This is an introduction to the FTA Highlights of a Decade series, which showcases the main findings, results and achievements of the CGIAR Research Program on Forests, Trees and Agroforestry (FTA) from 2011 to 2021. FTA, the world’s largest research-for-development partnership on forests, trees and agroforestry, started in 2011. This series features the work undertaken under the FTA program by its strategic partners: Center for International Forestry Research-World Agroforestry (CIFOR-ICRAF), The Alliance of Bioversity and CIAT, Centro Agronómico Tropical de Investigación y Enseñanza (CATIE), French Agricultural Research Centre for International Development (CIRAD), Tropenbos International and International Bamboo and Rattan Organisation (INBAR); and other national and international partners.